2011
DOI: 10.1158/0008-5472.can-10-1601
|View full text |Cite
|
Sign up to set email alerts
|

A Dual PI3K/mTOR Inhibitor, PI-103, Cooperates with Stem Cell–Delivered TRAIL in Experimental Glioma Models

Abstract: The resistance of glioma cells to a number of antitumor agents and the highly invasive nature of glioma cells that escape the primary tumor mass are key impediments to the eradication of tumors in glioma patients. In this study, we evaluated the therapeutic efficacy of a novel PI3-kinase/mTOR inhibitor, PI-103, in established glioma lines and primary CD133 þ glioma-initiating cells and explored the potential of combining PI-103 with stem celldelivered secretable tumor necrosis factor apoptosis-inducing ligand … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 35 publications
2
77
0
Order By: Relevance
“…This is exemplified by molecules that sensitize cancer cells to death receptor-mediated apoptosis, such as TNF-related apoptosis-inducing ligand (TRAIL; refs. 14, and [23][24][25]. We found that the combination treatment of GDC-0941 and ABT-263 exerted a stronger effect on loss of cellular viability in glioblastoma cells as compared with each compound alone.…”
Section: Discussionmentioning
confidence: 74%
“…This is exemplified by molecules that sensitize cancer cells to death receptor-mediated apoptosis, such as TNF-related apoptosis-inducing ligand (TRAIL; refs. 14, and [23][24][25]. We found that the combination treatment of GDC-0941 and ABT-263 exerted a stronger effect on loss of cellular viability in glioblastoma cells as compared with each compound alone.…”
Section: Discussionmentioning
confidence: 74%
“…This may be attributed to TRAIL-insensitive tumor cells resulting from the lack of TRAIL death receptors expression [7] and aberrant expression of pro-apoptotic or pro-survival molecules [8,9]. Accordingly, improved treatment strategies, such as the use of TRAIL coupled with other conventional or novel drugs for instance temozolomide (TMZ) [10], paclitaxel, carboplatin and bevacizumab [11], phosphoinositide-3-kinase (PI3K)/ mammalian target of rapamycin (mTOR) inhibitor PI-103 [12], Bortezomib [13], or histone deacetylase inhibitor Entinostat [14], have been explored to enhance the therapeutic efficacy mediated by TRAIL. In gliomas, a study has shown that the use of a gap junction (GJ) inhibitor, carbenoxolone (CBX), was capable of enhancing TRAIL, FasL, and etoposide-induced apoptosis through the disruption of cell-cell interaction [15].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their tumor-tropism, MSC have generated a great deal of excitement as a potential source of cells for cell-based therapeutic strategies. Genetic modification of MSC using viral vectors that carry therapeutic gene(s) has been shown to potentially inhibit tumor growth [10,12,24].…”
Section: Introductionmentioning
confidence: 99%
“…Although several mechanisms have been implicated in TRAIL resistance, in the present study we verified that treatment with MK886 had the potential to overcome TRAIL resistance by decreasing in the expression levels of antiapoptotic proteins related to the apoptotic signaling pathway at different stages of the caspase cascade, and increasing in death receptor-mediated apoptosis directly. In particular, several groups, including ours, have reported the use of MSCs expressing secretable TRAIL, which has been shown to be a potent anticancer agent in experimental glioma models (7,8,37,38) and found an effective therapeutic potential by overcoming some of the hurdles of conventional TRAIL-based treatments that use soluble rTRAIL protein or agonistic antibodies to DR5 (39,40). However, an additional issue with TRAIL-based therapy, that is, the resistance of tumor cells to TRAIL, remains unaddressed.…”
Section: Discussionmentioning
confidence: 99%